Tingkat Kegemukan dan Kebugaran Jasmani Siswa Sekolah Menengah Atas Berbasis Gender - Andicha G Jeki; Dwiko F Rizki (Universitas Batanghari Jambi, 2021)
Overweight and obesity are serious problems faced in the world, because it continues to increase in all countries. Riskesdas 2013 data shows that nationally, the problem of obesity in school-age children is quite high, namely adolescents at 10.8%. The main cause of obesity is a lack of physical activity which will have a direct impact on decreasing physical fitness. Physical education and sports in schools also aim to foster and develop children's potential in physical, mental, social, emotional, moral and even cognitive aspects. This study aims to see and analyze the level of obesity and physical fitness in high school students based on gender. The study was conducted in an observational manner with a cross sectional approach. The research location is Madrasah Aliah Negeri Cendikia Jambi. Respondents selected by purposive sampling of 56 respondents by comparing evenly, namely a number of 28:28 respondents based on obesity level and gender distribution. Data collected by filling questionnaires, anthropometric measurements, physical fitness tests. Data analyzed using chi square test with a significance value of p <0.05 at the 95% level of significance. The results showed 44:12 respondents in the study had a genetic history of obesity, 37 respondents aged <17 years and 19 respondents 17 years. The chi-square analysis results showed the p value = 0.00 (p <0.05) in men, which means there is relationship between obesity and physical fitness, and p value = 0.39 (p> 0.05) in women who means that there is no relationship between obesity and physical fitness. Strong relationships were simultaneously analyzed using binary logistic regression between variables, namely obesity, age, gender and genetic history, and it was found that obesity factors most influenced the dependent variable, namely physical fitness, indicated by the value of Exp. (B) 3, 60 and p value = 0.017.